An Alternative Teacher Preparation Journey - Debbie Mercer; Jim Barrett (The Advocate, 2011)
The following report discusses one university's alternative pathway journey. Four candidates were accepted into the program the first year in the fall of 2003. Since then numbers have increased to over 175 active program participants. Such substantial growth evidences the need for highly qualified teachers, especially in particular content areas and geographic regions as highlighted in the following report. State guidelines and regulation requirements help ensure quality, rigorous programs.